Robo-advisory for Islamic financial institutions: shariah and regulatory issues - Adam Sa'ad, Auwal; Syed Jaafar Alhabshi, Syed Musa; Hassan, Rusni; Mohd Noor, Azman (2019)
The paper aimed at investigating the potential Shari’ah and regulatory issues surrounding Robo-Advisors while adopting the relevant opinions and understanding of Shari’ah classical and contemporary scholars. It also seeks to examine the legal implications of Robo-Advisors in the Islamic financial industry and explore the technical requirements of this emerging phenomenon.